Left dural carotid cavernous fistula mimicking an inflammatory process: A case report - Annika K. Oie, BS; Amanda A. Herrmann, PhD; Michael H. Rosenbloom, MD (Radiology Case Reports, 2024)
A female in her 70s presented with altered mental status, left eye pain, ophthalmalgia, and diplopia following a fall. Brain MRI demonstrated contrast-enhancing left peri-insular T2 hyperintense changes that was read as possible herpes simplex encephalitis by neuroradiology. Cerebral angiogram revealed a Barrow Type D left sided carotid cavernous fistula. The patient was subsequently treated with endovascular transvenous coil embolization of the left cavernous sinus resulting in complete occlusion of the fistula. The goal of this case is to present a unique case of a carotid cavernous fistula radiologically mimicking herpes simplex encephalitis. Early recognition of carotid cavernous fistula on neuroimaging is important for prompt treatment of symptoms.